2021
DOI: 10.1038/s41467-021-21511-x
|View full text |Cite
|
Sign up to set email alerts
|

Improved protein structure refinement guided by deep learning based accuracy estimation

Abstract: We develop a deep learning framework (DeepAccNet) that estimates per-residue accuracy and residue-residue distance signed error in protein models and uses these predictions to guide Rosetta protein structure refinement. The network uses 3D convolutions to evaluate local atomic environments followed by 2D convolutions to provide their global contexts and outperforms other methods that similarly predict the accuracy of protein structure models. Overall accuracy predictions for X-ray and cryoEM structures in the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
242
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 205 publications
(247 citation statements)
references
References 35 publications
2
242
0
3
Order By: Relevance
“…To obtain the final refined structures, we need to assess and rank the generated models. Many methods for estimation of model accuracy have been described such as MULTICOM_CLUSTER [ 10 ], Pcons [ 58 ], PRESCO [ 59 ], DeepAccNet [ 60 ], and ProQ3D [ 61 ]. Here, for a quick ranking purpose, we use a widely used knee-based ranking method [ 49 ] in a multi-objective optimization problem to rank those models.…”
Section: Methodsmentioning
confidence: 99%
“…To obtain the final refined structures, we need to assess and rank the generated models. Many methods for estimation of model accuracy have been described such as MULTICOM_CLUSTER [ 10 ], Pcons [ 58 ], PRESCO [ 59 ], DeepAccNet [ 60 ], and ProQ3D [ 61 ]. Here, for a quick ranking purpose, we use a widely used knee-based ranking method [ 49 ] in a multi-objective optimization problem to rank those models.…”
Section: Methodsmentioning
confidence: 99%
“…Baker’s group recently developed a DL framework called DeepAccNEt [ 72 ] that estimates the error in every residue–residue distance along with the local residue contact error. DeepAccNEt consists of a series of 3D and 2D convolutional layers and predicts (i) error histogram (Cβ–Cβ distance error distribution), (ii) mask (native Cβ contact map with a threshold of 15 Å, (iii) and per residue Cβ local distance difference score (Cβ I-DDT) score.…”
Section: Deep Learning-based Advances In Various Steps Of Protein Structure Prediction Pipelinementioning
confidence: 99%
“…Treating a protein structural model as a graph, ProteinGCN [13], GraphQA [14] and VoroCNN [15] applied graph convolutional networks (GCN) to estimate the model accuracy. ResNetQA [16] and DeepAccNet [17] used deep residue networks to address the problem.…”
Section: Introductionmentioning
confidence: 99%
“…In CSAP13, DeepRank [5] demonstrated that accurate residueresidue contacts (a simplified representation of distances between residues) predicted by deep learning improved the prediction of the quality of protein structural models, suggesting that more detailed residue-residue distance predictions could further improve EMA. However, only a few methods [6], [16], [17], use residue-residue distances to estimate the accuracy of protein structural models.…”
Section: Introductionmentioning
confidence: 99%